Systematic Literature Review (SLR): Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Zulfa Arifia Rahmadani; Sherly Arinda May Listy; Dimas Agus Dwi S; Fina Fakhriyah; Erik Aditia Ismaya (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The cooperative learning model of the jigsaw mathematics learning type can present a new atmosphere in the learning process, increase students' interest and self-confidence, so that they actively participate in learning activities and class discussions. The purpose of this study is to increase self-confidence in group results and to be active with friends. The method used in this study uses the SLR (Systematic Literature Review) method. Data collection was carried out by documenting all articles with similar research in the research report used in this study 24 articles which then became 7 articles and the final 2 articles were national journals obtained from the Google Scholar database through the publish or perish application. In this study it was found that the mathematics learning model uses a jigsaw cooperative learning model to increase self-confidence, friendship, and activities with friends to learn mathematics.